Implementasi Kebijakan Pupuk Bersubsidi dalam Meningkatkan Ketahanan Pangan yang Berkelanjutan bagi Masyarakat : (Studi Kasus di Desa Benowo Kecamatan Bener Kabupaten Purworejo) - Adi Wahyono; Rani Pajrin; Sholihul Hakim (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Implementation of subsidized fertilizer policy does not run optimally in Benowo Village and supervision that has never been done by the Purworejo Agriculture Office or from BPP Bener are 2 problems that become the background of this research. The objective of this research was implemented policy on subsidized fertilizer which is focused on farmer groups in Benowo Village and to know the supervision subsidized fertilizer conducted by the Agriculture Office of Purworejo District as an institution authorized to manage subsidized fertilizer and the cooperation of other institutions or agencies related to it. The method of research used was qualitative. Collecting data is done at the research location namely Benowo Village by interview, observations, as well as documentation. After all the data has been collected, continued data selection based on similarities that proved the truth. Results with descriptive a method to accomplish valid research objectives. Research results and discussion obtained of the problem formulation was the implementation of the subsidized fertilizer policies in Benowo true existence is not running optimally because of the problem of fertilizer application that occurs. The second problem formulation is to produce a picture of supervision that is less attention from the Department of Agriculture regarding subsidized fertilizers. So that the resulting conclusions and also suggestions in essence that the Government and the Agriculture Office are more active in providing solutions to the problems of implementing policies and supervision of subsidized fertilizers in Benowo Village on an ongoing basis.